Analysis of the Characteristics of the Ethnoscience-Based Numeracy Test Instrument Using the Rasch Model - Muliani Muliani; Nanda Novita; Mellyzar Mellyzar; Ali Imron Pasaribu; Mhd. Ridwan Fadli (Postgraduate, University of Mataram, 2022)
The numeracy ability of students in Indonesia is in a low category based on PISA results from 2000 to 2018. So, efforts are needed to strengthen numeracy skills through the development of ethnoscience-based numeracy test instruments. The purpose of this study was to analyze the characteristics of the ethnoscience-based numeracy test instrument using the Rasch model. Â The subjects of this study were students of SMPN Arun and SMPS Sukma Bangsa, Lhokseumawe City, totaling 123 students. The number of questions to be analyzed in the test is 68 items. Analysis using Winsteps software. The results of the analysis showed that the ethnoscience-based numeration instrument in this study was declared reliable. 59 of the 68 items were said to be valid, with details of 32 valid items eligible to be used and 27 valid items needing to be revised for improvement before being used. This instrument can be used to measure subjects who have ethnoscience-based numeracy skills in the low, medium, and high categories, so to examine ethnoscience-based numeracy skills students can use this instrument.